NYANYIAN ANAK BALAM: TERAPI MISTIK PERDUKUNAN KE SENI PERTUNJUKAN RABAB PASISIE DI PESISIR SELATAN SUMATERA BARAT - Kamal, Zahara (Humanus, 2015)
This article is part of reserch,which reveals the problem of singing of anak balam in the context of shamanism entered the real of the performing art tradition of rabab pasisie in south pesisir.in the context of shamanism,the singing of anak balam serves as a means of communication between shamans and spirit of ancestor to identify a patient’s disease and type of medicine.while the singing of anak balam in context of performing arts rabab, serves as ameans of intertainment to enliven various local community activities.this reserch use a quanlitative method sosiology approach,antropology approach,easthetic approach.data colected through observasion, interview and documentation.this research found that in term of aesthetics singing of anak balam in context of shamanic different with the singing of anak balam in the context of art performing rabab pasisie, because in shamanism context eathetic value is not considered by shamans, because preferred here is to communicate with the spirit of ancestors,while in the context of performing arts rabab,aesthitic value higly considered by rabab artists both from the cultivation of musical and singing text.